Propuesta de mejoramiento de la productividad en una empresa metalmecánica mediante la aplicación de un VCM - Ordóñez Cazar, Marisol Stteffany (2017)
This degree work is a proposal for improving the productivity of a metal mechanic through use of Value Stream Mapping (VSM). The implementation of VSM aids in identifying non-value adding activities, prioritize them and determine areas where waste can be cut out. Through the use of VSM as well as other lean manufacturing tools the manufacturing process can be vastly improved. For the corresponding study, the family of wall furniture was chosen and within this the "furniture multi-product railings", being the most economically important product for the company, and the one that goes through all its areas and most of its processes, allowing the complete visualization and analysis of the flow throughout the value chain. In order to determine the improvement proposal, information was collected on the "furniture multi-product railings", the corresponding time study of the processes in which this product goes through was made and was compared with the takt time of the demand, thus obtaining opportunities for improvement in all those processes that, because they are very time consuming, prevent the delivery on time of the product and therefore negatively influence customer satisfaction. The proposed solutions vary according to the case and lean manufacturing tools are used with a continuous improvement approach for each situation. The improvements are represented in the diagram of a future VSM and results are estimated according to the activities defined in the improvement proposal. The result was an improvement in a 76,71% of the total productivity, a reduction in the lead time and the processing time of a 40,16 % and a 91,88 % respectively, an increase in the efficiency of the bottlenecks found and the increase of net profit in $35000 dollars in the production of the furniture under study.